2018
DOI: 10.4103/jpn.jpn_60_17
|View full text |Cite
|
Sign up to set email alerts
|

Cranial sonography in preterm infants with short review of literature

Abstract: Background:Premature newborn infants are exposed to a wide spectrum of brain lesions which are clinically silent supporting a possible role of cerebral ultrasound screening. Aim of the study is to describe the pattern of cranial ultrasound abnormalities in preterm infants defining the short term and long term neurologic outcomes.Material and Methods:A hospital-based bedside cranial ultrasound was carried out at day 1, 3, 7 and follow-up scan at 3-6 months in the Department of Radio-diagnosis.Results:One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
2
9
1
2
Order By: Relevance
“…The authors of the current study compared the predictive value of alarm symptoms appearing in the 9th month in respect of the 24th month, and confirmed their clinical significance in evaluating and forecasting the development of preterm baby. A predictive value for GM-S, FM-S and SO-EM was also observed when abnormal results of ultrasound examination at birth occurred, which has also been observed by other researchers [46].…”
Section: Discussionsupporting
confidence: 85%
“…The authors of the current study compared the predictive value of alarm symptoms appearing in the 9th month in respect of the 24th month, and confirmed their clinical significance in evaluating and forecasting the development of preterm baby. A predictive value for GM-S, FM-S and SO-EM was also observed when abnormal results of ultrasound examination at birth occurred, which has also been observed by other researchers [46].…”
Section: Discussionsupporting
confidence: 85%
“…In the group of premature babies, apart from prematurity, other developmental risk factors often co-exist: asphyxia, low body weight, and brain damage confirmed by imaging tests [38,39,40]. The results of the presented studies indicated that the dependence of the frequency of rehabilitation used on the degree of prematurity, asphyxia and low birth weigh, were not statistically significant.…”
Section: Discussionmentioning
confidence: 74%
“…Otro estudio más reciente (2018), Diwakar y Khurana, analizaron 100 recién nacidos prematuros, en los que detectaron diferentes anomalías en la ecografía craneal que incluyen hidrocefalia 12%, hemorragia intracraneal 6%, edema cerebral 6%, leucomalacia periventricular 2%, quiste del plexo coroideo 1%, septos intraventriculares 1% y colpocefalia 1% (17).…”
Section: Discussionunclassified
“…Desde la concepción hasta los primeros años de vida ocasionan anomalías, transitorias o definitivas, que pueden alterar la adecuada maduración del sistema nervioso central, repercutiendo en su desarrollo motor, sensorial, cognitivo o conductual, pudiendo conllevar a retraso y/o afección de su crecimiento y desarrollo norma Estos factores son también denominados alto riesgo biológico por algunos autores (1). Dentro de los factores de riesgo hay un primer grupo en el que se encuentran los neonatos con riesgo orgánico, aquellos con: trastornos cromosómicos, malformaciones congénitas mayores que precisaron cirugía, prematuridad (edad gestacional menor de 32 semanas), bajo peso al nacer (menor a 1500 gramos), peso inferior a 2 DS para su edad gestacional, asfixia severa, Apgar a los 5 minutos ≤ 3 puntos, ventilación mecánica prolongada, retraso de crecimiento intrauterino, infecciones congénitas y del sistema nervioso Salus.2021; 25(2): [9][10][11][12][13][14][15][16][17][18] Transfontanellar ultrasound findings in neonates and young infants with high biological risk.…”
Section: Introductionunclassified